Dune: The Butlerian Jihad / 1. - Herbert, Brian (Tor, 2002)
A prequel to Frank Herbert's science fiction classic, "Dune," that takes readers back ten thousand years, chronicling the war in which humans won their freedom from their "thinking machine" masters and showing how the houses of Atreides and Harkonnen became mortal enemies.